Formative Assessment: A Cognitive Perspective - Christos Theodoropulos (Working Papers in Applied Linguistics and TESOL, 2015)
The roles of attention and awareness in second language (L2) learning have been examined extensively in a number of SLA studies. One of the findings and claims made repeatedly is that attention as awareness at the level of noticing is a necessary condition for comprehensible input to be detected, selected, processed, and potentially and partially integrated within a learner’s internalized grammar – that is, to become intake (Gass, 1988, 2003; Leow, 1995, 1997, 2000, 2001, 2003; Robinson, 1995, 2003; Rosa & O’Neill, 1999; Schmidt, 1995, 2001; Swain, 1985, VanPatten, 1996). The purpose of this discussion is to briefly illustrate how findings from these studies and, specifically, concepts such as attention, noticing, and intake can help researchers and practitioners reconceptualize the processes involved in formative assessment at the planning and implementation stages.